2021
DOI: 10.1007/s00417-021-05187-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of intravitreal therapy for symptomatic diabetic macular oedema in a real-world setting in Switzerland

Abstract: Objective To assess the long-term visual outcomes in eyes with symptomatic diabetic macular oedema (DME) under intravitreal treatment (IVT) in a clinical routine setting. Methods Patients with newly diagnosed DME were included in this retrospective study if they had received at least three IVTs and a follow-up period ≥ 2 years. Due to altered treatment patterns since the approval of ranibizumab for DME in 2012, patients were subdivided according to their f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Here, the median number of injections for all patients was 5.0 in the first year, which fell to 3.0, 1.0, 0.0, and 0.0 in the 2nd, 3rd, 4th, and 5th years, respectively [ 19 ]. Zirpel et al reported Swiss long-term outcome data for 191 patients with DME and found that number of injections fell dramatically after the first year, and that loss to long-term follow-up was mainly due to discontinuation and referral back to the private ophthalmologist for screening and observation [ 20 ]. A multicenter retrospective study of 12 institutions in Latin America and Spain included 201 patients with DME for a study of 5-year outcomes after anti-VEGF therapy [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, the median number of injections for all patients was 5.0 in the first year, which fell to 3.0, 1.0, 0.0, and 0.0 in the 2nd, 3rd, 4th, and 5th years, respectively [ 19 ]. Zirpel et al reported Swiss long-term outcome data for 191 patients with DME and found that number of injections fell dramatically after the first year, and that loss to long-term follow-up was mainly due to discontinuation and referral back to the private ophthalmologist for screening and observation [ 20 ]. A multicenter retrospective study of 12 institutions in Latin America and Spain included 201 patients with DME for a study of 5-year outcomes after anti-VEGF therapy [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…From a healthcare planning perspective, it is important to understand the number of injections over time in relation to patient burden to better plan adequate treatment facilities and services [ 11 , 12 ]. Unlike neovascular age-related macular degeneration (AMD), which requires continuing treatment for years for the majority of patients [ 13 , 14 , 15 , 16 ], in DME, studies report that the burden of anti-VEGF treatment is mainly in the first years of therapy [ 17 , 18 , 19 , 20 , 21 ]. This circumstance for DME presents an entirely different consideration than, e.g., neovascular AMD, in terms of the number of patients in active therapy when planning a large-scale, anti-VEGF therapy service for DME.…”
Section: Introductionmentioning
confidence: 99%
“…This is of particular importance when considering the necessity of functional vision for these working-aged, relatively young patients with T1D. Accordingly, the benefits of early intensive treatment with anti-VEGF has recently been shown to result in satisfying long-term visual outcomes [ 23 ]. Even in the cases of no BCVA improvement, anti-VEGF treatment may improve contrast sensitivity in DME patients [ 20 ], and thus provide the best long-time safety in maintaining good visual function.…”
Section: Discussionmentioning
confidence: 99%
“…VEGF plays an essential role in diabetic retinopathy and is involved in the development of DME. As such, anti-VEGF therapies have shown efficacy in DME [9], and DME-related vision loss has decreased since their introduction [10,11]. Anti-VEGF therapy is now considered the standard of care, with additional laser photocoagulation and steroid injections as second-line options if required [12].…”
Section: Introductionmentioning
confidence: 99%
“…In 258 patients with DME, only 16% of patients had no fluid after 12 months of treatment with intravitreal aflibercept [30]. This lack of maintenance has been shown to differ depending on intensity of treatment, with increased healthcare visits and injection frequency associated with greater improvements in vision [11,26,31].…”
Section: Introductionmentioning
confidence: 99%